Studies on Benthic Fauna with relation to physio chemical parameters in Betana Wetland, Morang, Nepal - Karki, Samikshya; Shrestha, Jay Narayan (Our Nature, 2024)
This study examined the benthic fauna and its relation to the physic chemical parameters in Betana wetland, Morang, Nepal from December 2020 to May 2021. Over the course of six months, the study found two genera of Annelida (Hirudinea and Lumbricina), eight genera of Arthropoda (Macrobranchium, Chironomus, Cyclops, Cypridopsis, Blasturus, Diptera, Coeleptera, and Naupli), and four species of Mollusca (Bellamya bengalensis, Parreysia flavidens, Lamellidens marginalis, and Indoplanorbis exutus). Arthropods were more prevalent in the spring due to the increase in temperature. The average maximum water temperature was 23.66°C in the spring and the minimum was 20.25°C in the winter. The maximum soil temperature was 24.9°C in the spring and the minimum was 21.08°C in the winter. The pH was highest in the spring (7.67) and lowest in the winter (7.21). The highest dissolved oxygen (DO) was found in the winter (7.6 mg/l) and the lowest was in the spring (7 mg/l). The maximum free CO₂ was found in the spring (26.83 mg/l) and the minimum was in the winter (21.25 mg/l). Total alkalinity was highest in the spring (113 mg/l) and lowest in the winter (105 mg/l). Total hardness was highest in the spring (83.51 mg/l) and lowest in the winter (69.25 mg/l). Water temperature and soil temperature had a high correlation coefficient (0.93) with benthic fauna, while DO and pH showed a high negative correlation coefficient (-0.93 and -0.92), respectively.